Validation of educational materials for an online course aimed at promoting water consumption among middle-school adolescents in Mexico - Salazar-Coronel, Araceli Apolonia; Jiménez-Aguilar, Alejandra; Uribe-Carvajal, Rebeca; Chávez-Becerril, Graciela Berenice; Pérez-Jiménez, Ana Karen; Shamah-Levy, Teresa (Revista Española de Comunicación en Salud, 2023)
Introduction: Validating health-education materials prevents the dissemination of erroneous messages and enhances the effectiveness of health-promotion initiatives. Objective: To describe the validation process for five educational materials pertaining to an online course on the promotion of water consumption among Mexican adolescents. Methodology: One group of 13-15 experts (technical validation) and another of 13-39 adolescents (population validation) reviewed three infographs and two videos using digital tools. Five criteria were established for the evaluation: appeal, clarity, identification, acceptance and inducement to action. A performance index was developed based on two categories: strong or weak compliance with each criterion. Successful compliance was determined when 70% or more of responses fell within the strong-compliance category. Results: Between 80% and 100% of the experts and adolescents rated all materials in the strong-compliance category for appeal, acceptance, clarity and inducement to action. For identification, however, the experts accorded the three infographs low scores, with similar results obtained from the adolescents for the three infographs and one video. Conclusions: Validation of the course materials allowed for identifying their strengths and weaknesses, as well as for ascertaining their usefulness in promoting water consumption among Mexican adolescents.